Applied math for security : a Pythonic introduction to graph theory and computational geometry - Reilly, Daniel (Security researcher) (No Starch Press, 2023)
"A math-based guide for information security practitioners. Teaches how to use concepts from various fields of mathematics, such as graph theory, computational geometry, and statistics, to create and implement ready-to-use security tools. Features code examples in Python and hands-on proof-of-concept projects for solving real-world problems"--